Menafsirkan Tanda-tanda Bedah Plastik: Analisis Semiotik - Ika Aliyatur; Shanty Duwila; Yulis Setyowati (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2023)
This study utilizes Charles Sanders Peirce's semiotic framework, concentrating on the interpretation of signifiers associated with plastic surgery. A particular emphasis is placed on the